Effects of phytobiotics (biomin® p.e.p.) on nursery pig performance - Sulabo, R.C.; Jacela, J.Y.; Neher, F.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 192 weanling pigs (initially weighing 12.9 lb and 22 ± 2 d of age, PIC) were used in a 42-d growth assay to determine the effects of phytobiotic (Biomin® P.E.P. 125 and 125T) addition to nursery pig diets on post-weaning growth performance. Pigs were blocked by initial weight and randomly allotted to one of four treatments: 1) negative control (feed containing no antibiotic or phytobiotic); 2) negative control + phytobiotic 1 (125 g/ton of Biomin® P.E.P. 125); 3) negative control + phytobiotic 2 (125 g/ton of Biomin® P.E.P. 125T), and 4) positive control (feed containing 140 g/ton of neomycin sulfate and 140 g/ton of oxytetracycline HCl; Neo/OTC). Each treatment had six pigs per pen and eight replications (pens). Phase 1 and Phase 2 diets were fed from d 0 to 14 and d 14 to 42 post-weaning, respectively. Pigs were weighed and feed intake was determined weekly to calculate ADG, ADFI, and F/G. Data were analyzed as a randomized complete block design using the MIXED procedure of SAS with pen as experimental unit. Overall (d 0 to 42), pigs fed Neo/OTC had greater ADG (P<0.03) and ADFI (P<0.01) than pigs fed the negative control or diets with phytobiotics. Addition of phytobiotics to the nursery diet also increased (P<0.02) daily gains (5.3 to 6.1%) and reduced (P<0.01) F/G (3.5 to 4.0%) compared to pigs fed diets without antibiotics. No differences (P>0.38) were observed in ADFI between pigs fed the negative control diet and pigs fed either phytobiotic. Pigs fed diets containing either phytobiotic had improved (P<0.01) F/G compared with pigs fed diets with Neo/OTC. However, pigs fed diets with Neo/OTC had similar (P=0.26) F/G compared to pigs fed diets without antibiotics. No differences (P>0.52) were observed in ADG, ADFI, and F/G between pigs fed diets with phytobiotic 1 and 2. In conclusion, phytobiotics in nursery diets improved post-weaning growth performance compared to pigs fed diets without antibiotics. However, the improvement in growth rate was intermediate between diets fed with and without in-feed antibiotics. Further research is needed to elucidate specific modes of action that caused positive effects in post-weaning growth and efficiency.
Keywords: Swine; Antibiotics; Phytobiotics